American Civil Society and Democracy Promotion in the Arab Gulf States after 9\11: Strategies, Organizations, and Multisectoral Impact - Azam, Muhammad (Annals of Human and Social Sciences, 2024)
As the American government placed a greater emphasis on the objective of advancing democratic values and awareness in the Arab world in the aftermath of 9/11, the private sector also became more focused on this front. Governmental and nongovernmental American organisations collaborated together. In what ways did American civil society and proponents of democracy contribute to the post-9/11 goal for democratic expansion and reform in Arab Gulf states? An attempt to address this question is made in this article. The paper discusses the methods used, the aims and objectives established, and the plans and strategies developed and implemented by American private sector and civic society. The awareness campaign and the research enterprise’s role are dealt with. There is also discussion of the actions and endeavours undertaken in the fields of politics, education, and culture. The American nongovernmental sector played a considerable role in advancing women’s empowerment, human rights, and media freedom.